Admission hyperglycemia and adverse clinical outcomes in critically ill patients: A prospective, observational study - Jain, Vishakha; Bade, Sunil; Gupta, O (Journal of Diabetes and Endocrine Practice, 2021)
Background: Admission hyperglycemia is known to cause increase in in-hospital mortality, increased length of intensive care unit (ICU) stay, increased morbidity across critically ill patients. In patients with vascular disease (myocardial infarction, stroke, etc.), this has been extensively studied. We planned to study the prevalence of admission hyperglycemia and its association with adverse outcomes in all critically ill patients. Methods: In an observational, prospective study, 200 critically ill inpatients admitted to the medicine ICU were included. The patients were stratified into known diabetes, newly detected diabetes, and stress hyperglycemia. Baseline clinical and laboratory parameters were collected, and Acute Physiology and Chronic Health Evaluation (APACHE)-II, Sequential Organ Failure Assessment (SOFA), and Simplified Acute Physiology (SAP II) scores were calculated. Data regarding clinical outcomes (discharge or in-hospital death) were also collected. Results:   The prevalence of admission hyperglycemia and of stress hyperglycemia was found to be 11.99% and 1.51%, respectively. The newly detected diabetes had higher admission hyperglycemia and glycosylated hemoglobin. The prognostic scores – APACHE-II, SAP II, and SOFA scores – were worse among patients who died in the newly detected diabetes and the stress hyperglycemia group but not in the known diabetes group.   The odds of death increased by 3.5 times with 1-day increase in the ICU. Conclusion: Our study concluded that the patients with newly detected diabetes and stress hyperglycemia had more severe illness as compared to the known diabetics.
Keywords: Admission hyperglycemia; clinical outcomes; critically ill patients; diabetes mellitus; hyperglycemia; mortality; stress hyperglycemia